Enquiry-based science in the infant classroom: 'letting go'. Issue 2 (2nd April 2016) - Byrne, Jenny; Rietdijk, Willeke; Cheek, Sue
ABSTRACT: Enquiry-based science in primary classrooms is key to encouraging children's interest and curiosity about the world around them and as a result helps to stimulate their understanding and enjoyment of science. Yet many primary teachers lack the confidence to implement enquiry-based approaches effectively. The reasons are myriad and often result in the teacher controlling and orchestrating the lesson leaving little room for children's exploration and autonomy. This paper explores how one infant school teacher was willing to relinquish control and 'let go' and expand her pedagogical repertoire to manage the many obstacles to including enquiry-based science in her classroom. The autonomy the children were given resulted in genuine enquiry-based science with the consequential benefit to their learning. Furthermore the teacher's confidence and self-efficacy seem to have been raised ensuring that that she would continue to include enquiry-based science as part of her practice in the future. As a model for other primary teachers this approach could help them overcome their reticence to engage with enquiry-based science.